Academic and special libraries : their working, problems, and solutions - Saxena, R. S. (Radhey Shyam), 1927- (Agra, India : Y.K. Publishers, 1989)
Indian situation.
Includes index.
Keywords: Academic libraries -- India; Special libraries -- India